Applying Green Hotel to Enhance Service Quality of the Front Office Staffs at Mercure Bali Legian - Ni Kadek Putri Wulandari; Nyoman Mastiani Nadra; Ni Ketut Bagiastuti; Ni Nyoman Triyuni (International Journal of Glocal Tourism, 2023)
Purpose : This study aims to analyze the application of green hotels in an effort to improve the service quality of front office staffs at Mercure Bali Legian and to identify indicators that need to be improved and maintained in the service quality of front office staffs at the hotel. Research methods : A questionnaire is distributed to respondents. The analytical technique is descriptive qualitative analysis to determine the application of green hotels at Mercure Bali Legian and quantitative analysis, namely importance performance analysis (IPA) is used to classify service quality indicators that need to be improved and maintained into a Cartesian diagram. Findings : Write only the main results and discussion in a few words. There is no discussion or explanation. Implications : There are five indicators that the front office staffs need to maintain the quality of service, namely the hotel lobby indicator is clean and smoke-free, supports the environmentally friendly concept during the check-in process by minimizing the use of paper, the staffs inform the hotel facilities including energy-saving facilities in the hotel, giving welcome drink using drinks from local products, and front office staffs providing information about the cashless program.